Kepemimpinan, Total Quality Management, Perilaku Produktif Karyawan, Kinerja Karyawan dan Kinerja Perusahaan - Ida Ayu Andini Wiandari; Gede Sri Darma (Universitas Pendidikan Nasional, 2017)
The purpose of this study is to determine the effect of Total Quality Management (TQM) on leadership, employee productive behavior, employee performance and company performance. The design of this study is quantitative, is the relationship of causality between variables. The study was conducted at Central General Hospital Sanglah. Data collection techniques used questionnaires to 115 employees. Data were analyzed by data analysis technique Structure Equation Modeling with AMOS program. The result of the research shows that the effect of total quality management on leadership is significant, the effect of total quality management on employee productive behavior is significant, the effect of total quality management on employee performance behavior is significant, the effect of total quality management on the company's performance is significant, the influence of leadership on productive behavior Employees are significant, the influence of leadership on employee performance is significant, the influence of leadership on the company's performance is significant, the effect of employee productive behavior on employee performance is significant and the influence of employee performance on company performance is significant.